The Relationship Between The Five Pillar Implementation And Quality Of Life In Type II Diabetes Mellitus Patients - Agnes Silvina Marbun; Normi Sipayung; Erwin Silitonga (TOUR HEALTH JOURNAL, 2022)
Backgorund: Diabetes mellitus is diabetes or blood sugar disease which belongs to the group of chronic diseases characterized by increased blood sugar levels. To improve the quality of life of type II DM patients, it can be done through the implementation of five pillars, namely education, fulfillment of nutrition, exercise, pharmacological therapy and monitoring of blood sugar levels. Purpose: The purpose of this study was to determine the relationship between implementation of the five pillars and quality of life in patients with type II diabetes mellitus. Method: The research method used is using a quantitative method with a cross sectional approach. The sampling technique in this study was accidental sampling, which consisted of 40 samples. The research instrument used was a questionnaire consisting of a five pillar implementation questionnaire with 15 statements and a quality of life questionnaire with 12 questions. Results: The results showed that the majority of respondents had a good implementation of the five pillars totaling 23 respondents (57.5%) and a good quality of life for the majority of them amounting to 32 respondents (80%). The results of the research data used the Spearman Rho test which showed that there was a relationship between the implementation of the five pillars and the quality of life in patients with diabetes mellitus type II at the Batang Beruh Health Center with pvalue = 0.003 p <0.05 with a value of r = 0.455, thus it can be concluded that the better the implementation five pillars, the better the quality of life of type II diabetes mellitus patients. Discussion & Conclusion: Therefore, this research is expected to encourage patients to carry out the implementation of the five pillars so that the quality of life of type II diabetes mellitus patients is good.